Peripheral venous access devices for apheresis: 16‐gauge is not always needed. Issue 3 (10th February 2020) - Mustieles, María‐Jesús; Acosta, Maria; Cid, Joan; Jiménez, María; Mateo, Dolors; Andreu, Bienvenida; Alba, Cristina; Perea, Dolores; Lozano, Miquel
Abstract : BACKGROUND: Peripheral venous access (PVA) devices for apheresis should be selected to provide enough flow with the least vein damage, but little information is available about PVA devices blood flow rates. The aim of this study was to know the blood flow rates provided by the most frequent PVA devices used in apheresis procedures. STUDY DESIGN AND METHODS: An experimental study was designed to simulate a plasma exchange procedure using citrated whole blood (WB). Two steel needles (16‐ and 17‐gauge [G]) and six plastic cannulas (16G, 17G, two 18G, 20G, and 22G) were analyzed. The hematocrit of the WB was adjusted to 45%, 40%, 35%, 30%, and 25%. The separated plasma from the WB was used as replacement fluid. RESULTS: Blood flow rate (inlet/return, mL/min) for 16G and 17G devices with a hematocrit of 45% was 142/142 (maximum admitted by separator); one of the 18G cannulas reached 142/142 and the other one reached 117/140; the 20G cannula reached 78/94; and the 22G reached 45/55. A hematocrit reduction from 45% to 25% increased the flow rate (when possible) over 22% (range: 14%‐30%). CONCLUSIONS: PVA devices with a size of 16‐18G provided the maximum flow admitted by the apheresis system. The 20G provided flow rates for a significant number of procedures, and 22G could be used in some procedures. The hematocrit should be taken into account when selecting the PVA device since, at hematocrit of 25%, the flow can be from 14% to 30% higher than flow rates reached with blood at hematocrit of 45%.